2014
DOI: 10.1103/physrevb.90.125155
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the interfacial magnetic anisotropy in multiferroic field-effect devices

Abstract: Ferroelectric field-effect devices based on perovskite oxide materials offer a new possibility to exploit emergent interfacial effects such as the electrostatic modification of the transport and magnetic properties of strongly correlated materials and to prove the magneto-electric coupling at the interface between the two different ferroic materials. Here we report on the reversible modulation of the interfacial magnetic and magnetotransport properties of La 0.825 Sr 0.175 MnO 3 thin films induced by switching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…A few XPS reports are also available in the literature on PZT/LSMO heterostructures; however, a thick layer of PZT restricts the investigation of chemical and valence states of layers close to interface. 17,18 Preziosi et al 10 have carefully demonstrated the transport properties of LSMO (5 nm) under two different polar states of PZT, which revealed that ferroelectric polarization significantly changes the interfacial magnetic anisotropy and affects the spin-orbit coupling. Leufke et al 11 have shown significant modification of magnetization of LSMO (7.…”
mentioning
confidence: 99%
“…A few XPS reports are also available in the literature on PZT/LSMO heterostructures; however, a thick layer of PZT restricts the investigation of chemical and valence states of layers close to interface. 17,18 Preziosi et al 10 have carefully demonstrated the transport properties of LSMO (5 nm) under two different polar states of PZT, which revealed that ferroelectric polarization significantly changes the interfacial magnetic anisotropy and affects the spin-orbit coupling. Leufke et al 11 have shown significant modification of magnetization of LSMO (7.…”
mentioning
confidence: 99%
“…Since the PHE signal in LSMO is orders of magnitude larger than that in ferromagnetic metals and not sensitive to the CMR background as the AMR [24][25][26], it is an ideal tool for high precision measurement of the magnetization orientation. All PHE measurements were taken at 100 K to achieve optimized signal [16,23,24].…”
mentioning
confidence: 99%
“…For nanostructured samples with small dimensions, magnetization cannot be obtained from direct magnetometry measurements, but can be sensitively probed by magnetotransport techniques such as anisotropic magnetoresistance (AMR), PHE, and anomalous Hall effect [22][23][24][25][26][27]. The PHE is the sinusoidal dependence of the transverse (ρ xy ) resistivity on the angle between the in-plane magnetization and the current direction ( Fig.…”
mentioning
confidence: 99%
“…2 There are numerous reports on voltage control of magnetization (see, e.g., reviews, 1-4 references therein, and recent Refs. 5 11), whereas for electric field effects on the anisotropic [12][13][14][15][16][17][18][19][20] and giant 13,21,22 [4][5][6][7][8][9][10][11]13,14,16,17,20 In such structures, upon application of an electric field, the piezoactive substrate induces a strain in the ferro(i)magnetic film and hence modifies its magnetic properties due to the magnetoelastic coupling effect. The (011) cut is particularly suitable because of the possibility of obtaining a high and well-defined uniaxial anisotropy by inducing simultaneously compressive and tensile strains in orthogonal [100] (x) and [011] (y) in-plane directions due to the different signs of d 31 and d 32 piezocoefficients.…”
mentioning
confidence: 99%